Comparative Effects of Profitability and Risk Management on Financial Stability in A Dual Banking System: Does Yield Matter? - Nur Izza, M. Yusril Hafidz; Putri, Amila Zamzabila (Jurnal Ilmu Ekonomi Terapan, 2024)
This study aims to examine the impact of risk management and profitability on the stability of conventional and Islamic commercial banks in Indonesia and to assess whether yield can moderate this effect. The research analyzes data from Indonesian Sharia and conventional commercial banks from 2016 to 2023 using fixed-effects panel data regression with robust standard errors. The findings reveal that Sharia banks exhibit greater risk resilience than conventional banks, demonstrating a lower probability of instability. Additionally, yield enhances the effect of non-performing financing (NPF) on bank stability in Sharia banks and mitigates the impact of non-performing loans (NPL) in conventional banks. These results offer valuable insights for policymakers and contribute to the literature by highlighting the need for a balanced approach to ensure that bank profitability enhances stability rather than undermines it. It underscores that higher profits are not inherently beneficial, nor are lower profits necessarily detrimental. Banks must strike a balance, maintain public trust, and promote prudent risk management to achieve long-term stability.